‘The mirage of action’: Exploring the social work professions’ perpetuation of white supremacy through ‘Well-Intentioned’ actions - Aguilar, Jemel P.; Counselman-Carpenter, Elisabeth (Advances in Social Work, 2021)
This autoethnographic study highlights complex strategies for maintaining white supremacy used by “well-intentioned” heterocentric white female social workers that are enacted under the guise of practicing anti-racism in social work practice settings, classroom environments, policy initiatives, and advocacy work. Using autoethnography was both unplanned and deliberate. Unplanned, we needed a research method that allows us to explore the untouchable subject of heterocentric white female social workers and deliberate in that we could use our experiences to break ground and establish white supremacy among heterocentric white female social workers that espouse anti-racist values as an area of study. We draw on education, anthropology, sociology, and other disciplines to name some of the ongoing challenges to dismantling racism, colonialist, and reformer narratives in social work, and identify strategies used by all white folx, but particularly heterocentric white female social workers to neutralize the suggestion or accusation of their acts as racism. We name three challenges to dismantling racism among heterocentric white female social workers: hiding behind the data, anti-racist book clubs, and crying and comfort. We conclude with further questions for those who hold power in the field and a reflection upon our own continued intersecting struggles with these concepts. © 2021 Authors,.
Keywords: dept.swk; peer-reviewed